2014
DOI: 10.1016/j.egypro.2014.10.321
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design Methodology for Solar Concentrators Subjected to Wind Loads

Abstract: This paper develops and applies a new methodology for the structural design of solar concentrators under wind loads using the method of Finite Element Analysis (FEA), in order to obtain information on the structural characteristics to guarantee that the concentrator operation works under high wind loads.This methodology is applied to design a Scheffler Type Solar Concentrator (STSC) coupled to a Stirling engine in the city of Mexicali, B.C and the numerical results of this analysis allow to establish the mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Ruelas et al 65 used Finite Element Analysis to analyze the structural integrity of STSC under wind loads. Their analysis showed that a 12.4 m 2 reflector, when subjected to wind load of 180 km/hour undergoes deformations of about 0.005 m and resulted in a maximum stress of 27 MPa.…”
Section: Scheffler-type Solar Concentratormentioning
confidence: 99%
“…Ruelas et al 65 used Finite Element Analysis to analyze the structural integrity of STSC under wind loads. Their analysis showed that a 12.4 m 2 reflector, when subjected to wind load of 180 km/hour undergoes deformations of about 0.005 m and resulted in a maximum stress of 27 MPa.…”
Section: Scheffler-type Solar Concentratormentioning
confidence: 99%
“…The estimated maximum torsion moment [32] caused by wind action over the PV system area (A) of 4 m 2 is 1306 N-m, which assumes a density of air (δ) at sea level of 1.2 kg/m 3 at a distance (d) of 1 m and is based on Equation 3:…”
Section: Testingmentioning
confidence: 99%
“…He also found that India and other countries use the Scheffler reflector‐type solar cookers in various consumable sectors which defeated the society's cultural perception. Ruelas et al 30 fabricated the model of Scheffler‐type solar concentrator which could be applied in heavy wind loads of up to 180 km/h. A 12.4 m 2 designed reflector area was subjected to 0.005 m deflection only and attained 27 MPa maximum stress.…”
Section: Introductionmentioning
confidence: 99%